2006
DOI: 10.1007/s00264-006-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in preoperative function of patients undergoing total knee arthroplasty

Abstract: The prevalence of osteoarthritis is high in all ethnic and demographic groups. The timing of surgery is important because poor preoperative functional status is related to poor postoperative function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…In the Hispanic community, low arthroplasty rates may translate to less opportunity for knowing someone who has had an arthroplasty [7]. Joshy et al [16] found similar lower preoperative KSSs when comparing Asians with Caucasians. Chang et al [5] theorized that as Caucasian men ask the most questions during examinations, most medical literature available to patients address concerns of Caucasian males.…”
Section: Discussionmentioning
confidence: 99%
“…In the Hispanic community, low arthroplasty rates may translate to less opportunity for knowing someone who has had an arthroplasty [7]. Joshy et al [16] found similar lower preoperative KSSs when comparing Asians with Caucasians. Chang et al [5] theorized that as Caucasian men ask the most questions during examinations, most medical literature available to patients address concerns of Caucasian males.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom severity such as pain might be manifested differently in other ethnic populations [13]. Recent studies reported the existence of ethnic differences in symptom manifestation in OA population even in the same geographical area [17,21]. These ethnic differences may be explained by differing biological (genetic), social, and cultural factors between ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Poor health literacy, financial constraints, cultural influences and concerns about possible outcomes are amongst reported reasons for a lower willingness to undergo surgery and delayed presentation [96][97][98][99][100]. As such self-reported baseline pain and function are worse amongst ethnic minorities presenting for total joint replacement surgery [100][101][102][103].…”
Section: Culture and Ethnicitymentioning
confidence: 99%